Cyberbiosecurity in biointelligent environments: Integrating artificial intelligence, synthetic biology and automation in vital sectors (Research, Society and Development, 2025)
This study aims to analyze the importance of cybersecurity in the context of systems related to the biological sciences in different sectors of the economy, which is called cyberbiosecurity. A narrative bibliographic survey was carried out. Technological innovation has become an inherent aspect of our society's existence, since practically every item relevant to our daily lives has at least one cyber component associated with it. These include personal computers, computer networks, information technology and virtual reality. Life sciences are now interfacing with information technology and cyber security. This convergence has resulted in significant growth in the biotechnology sector and its applications in health, agriculture, manufacturing, automation, artificial intelligence and synthetic biology. This has necessitated the creation of a discipline that encompasses the scope of biosecurity and cyber-physical security and cyberbiosecurity which has been termed cyberbiosecurity which involves the understanding, protection, mitigation, investigation and attribution of unwanted surveillance, intrusions and malicious and damaging activities that may occur within or at the interfaces of the medical and life sciences, affecting security, competitiveness and resilience.